Land Degradation Due To Mining: The Gunda Scenario - Mbaya, Rejoice Paul (International Journal of Geography and Geology, 2013)
Several studies have been carried out on the effects of mining on the environment, these have been characterized by landscape devastation, deforestation, it has also exposed the land to both wind and water erosion, water pollution and other environmental hazards which poses threat to humans in diverse ways. The study is set out to examine land degradation due to mining in Gunda area of Biu plateau with emphasis on the landscape. Both primary and secondary data were used. The nature of the environment such as destruction to the landscape, lost in vegetation cover, scattered open pits, alteration of water courses etc were all considered. One of the findings revealed that mining has led to the discovery of diatomite in the pits along stream channels which they use locally for painting purposes in building. The findings further revealed that reclamation work may not likely take place soon, because there are no economic returns from it. The study therefore, recommended among others, that reclamation be encouraged by using some of the pits for wastes disposal with farm and household residues so as to refill it especially those on farmlands, also measures should be taken by the inhabitants in restoring back the altered stream channels to their former glory by filling the cuts.